2022
DOI: 10.3389/fvets.2022.969414
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Block recession calcaneoplasty of the calcaneal tuber for treating lateral superficial digital flexor tendon luxation in a dog

Abstract: A 4-year-old, intact, female, Collie was presented with 5 month history of right hindlimb lameness. Lateral luxation of the superficial digital flexor tendon (SDFT) was diagnosed on the basis of the clinical, radiographic and ultrasonographic finding. Intraoperatively, shallow right calcaneal tuber was observed. Block recession calcaneoplasty with retinaculum repair using anchor screw were performed to manage SDFT luxation. Additionally, temporary restraining pin was placed on lateral aspect of the calcaneal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A more recent case report described a block recession calcaneoplasty of the calcaneal tuber with retinaculum repair using an anchor screw and a temporary restraining pin for treating lateral SDF tendon luxation in a dog. In these studies, clear evidence of bone deformity was not observed in the radiographic images, but a flattened calcaneal groove was observed intraoperatively [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent case report described a block recession calcaneoplasty of the calcaneal tuber with retinaculum repair using an anchor screw and a temporary restraining pin for treating lateral SDF tendon luxation in a dog. In these studies, clear evidence of bone deformity was not observed in the radiographic images, but a flattened calcaneal groove was observed intraoperatively [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…It is our opinion that in all dogs with SDF tendon luxation and predisposed factors (obesity, misalignment, and hyperactivity), not only in patients with calcaneal dysplasia, the deepening of the groove can give greater stability to the tendon and promote the healing of the retinaculum, which otherwise would be continuously stressed. In the literature, a period of postoperative immobilizations ranging from 4 to 8 weeks order to avoid surgical treatment failure is recommended [2,[4][5][6][7]17,18] and, recently, colleagues have observed that the limb immobilization of 6 weeks or longer did not significantly affect surgical outcomes [13]. Contrary to what is suggested by the literature, all three of our patients did not need a postoperative immobilization of the tarsal joint following SDF tendon luxation repair because the deepening of the groove ensures tendon stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation